The Influence of Storytelling Methods on Early Childhood Expressive Language Skills - Sesilia Dea Lestari; Evie Palenewen; Fachrul Rozie (EDUJAVARE: International Journal of Educational Research, 2026)
Early childhood education is a level of education before basic education which is a coaching effort aimed at children from birth to the age of six. This study aims to determine the influence of storytelling methods on early childhood expressive language skills. The research method used is experimental. The sampling technique uses a pre-experimental design while the data collection technique is in the form of an initial test (pretest), treatment and final test (posttest). The sample in the study consisted of 9 children, consisting of 5 girls and 4 boys. Based on the results of the n-gain calculation, which is a normalized gain of 0.6 < 0.7 with a percentage of 0.60 or 60.80. It is included in the medium category, which means that the method of storytelling for early childhood expressive language skills is included in the category of quite effective. This study shows that the ability of expressive language in children such as children's ability to answer more complex questions, children's ability to group pictures in storybooks, the ability to communicate orally by having vocabulary, and the ability to express opinions in simple sentences and also retell the content of the story.